(untitled) (Experimental biology, 2015)
Gene silencing is an important regulatory and defense mechanism in plants. Plant viruses evolved some proteins that suppress cellular RNA interference mechanism. In this work identification of silencing suppressors of potato virus M (PVM) is reported. The cDNA sequences of different PVM open reading frames were cloned into the Gatewaycompatible binary T-DNA destination vector pMDC32, harboring a double 35S promoter. Each of these constructs was electroporated into Agrobacterium tumefaciens which then were agroinfiltrated into Nicotiana benthamiana 16C line. It was shown that viral coat protein (34K) as well as 12K protein possessed suppressor properties of cellular silencing activity. Thereafter, these open reading frames were cloned in both sense and antisense sequences into pUC19.